Aihu huanjing - Chen Jiahua,
'Love and protect the environment.' Fourth sheet of the "Four loves" Educational Propaganda Posters. Setno. 85394.1674. Made in the spirit of the Outline for the Implementation of Patriotic Education of the Propaganda Department. See also BG E15/134-7.